2019
DOI: 10.29252/jafm.75.253.29097
|View full text |Cite
|
Sign up to set email alerts
|

Double-Diffusive Bioconvection in a Suspension of Gyrotactic Microorganisms Saturated by Nanofluid

Abstract: This paper focuses on analytical and numerical investigation of double-diffusive bioconvection in a porous media saturated by nanofluid using the modified mass flux condition. Normal mode technique is employed to solve the governing equations of the Brinkman-Darcy model. The Galerkin weighted residual method (singleterm and six-term) is used to obtain numerical solution of the mathematical model. It is found that due to the presence of gyrotactic microorganisms, Rayleigh number is decreased substantially which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
7
2
Order By: Relevance
“…Transport of heat for the ferromagnetic fluid with thermal stratification over a stretching sheet was examined by Muhammad et al [22]. Saini and Sharma [23] extended the application of nanofluids through the investigation of double-diffusive bioconvection. Further extensive research and applications of nanofluids across numerous fields are heat transmission, energy, microequipment, and boiling applications [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Transport of heat for the ferromagnetic fluid with thermal stratification over a stretching sheet was examined by Muhammad et al [22]. Saini and Sharma [23] extended the application of nanofluids through the investigation of double-diffusive bioconvection. Further extensive research and applications of nanofluids across numerous fields are heat transmission, energy, microequipment, and boiling applications [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Equations (2) and (3) are momentum equations in x and y directions, respectively, based on Darcy–Boussinesq approximation. Equations (4)–(6) represent conservation energy, conservation of solute, and conservation of oxygen concentration, respectively 23 . Equation (7) represents the cell conservation of oxytactic microorganism 10 …”
Section: Formulation Mathematical Modelmentioning
confidence: 99%
“…He showed that the existence of gyrotactic microorganisms has a destabilizing effect on the system. Some recent analyses of nanofluid behaviour in the presence of gyrotactic microorganisms are given by Tham et al [17], Uddin et al [18], Saini and Sharma [19,20] among others.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticle diameter (expressed in nanometres) satisfies 𝑑 𝑝 ∈[11, 50] for a DW/alumina nanofluid and 𝑑 𝑝 = 29 for a DW/cupric oxide nanofluid, and φ ∈ [0.01, 0.1]. Khanafer and Vafai[38] also proposed that the effective dynamic viscosity follows the constitutive model for nanoparticle diameters (expressed in nanometres) satisfying 𝑑 𝑝 ∈[13, 133] and for Celsius temperatures 𝑇 ∈[20, 70]. Here 𝑎 1 , 𝑎 2 , … , 𝑎 8 and 𝑏 0 , 𝑏 1 , … , 𝑏 8 are constants.…”
mentioning
confidence: 99%